Reference equations for evaluation of spirometry function tests in South Asia, and among South Asians living in other countries. Issue 6 (1st December 2022) - Leong, Wei Yee; Gupta, Ananya; Hasan, Mehedi; Mahmood, Sara; Siddiqui, Samreen; Ahmed, Sajjad; Goon, Ian Y.; Loh, Marie; Mina, Theresia H.; Lam, Benjamin; Yew, Yik Weng; Ngeow, Joanne; et al.
Background: There are few data to support accurate interpretation of spirometry data in South Asia, a major global region with a high reported burden of chronic respiratory disease. Method: We measured lung function in 7453 healthy men and women aged ≥18 years, from Bangladesh, North India, South India, Pakistan and Sri Lanka, as part of the South Asia Biobank study. First, we assessed the accuracy of existing equations for predicting normal forced vital capacity (FVC), forced expiratory volume in 1 s (FEV1 ) and FEV1 /FVC ratio. Then, we used our data to derive (n=5589) and internally validate (n=1864) new prediction equations among South Asians, with further external validation among 339 healthy South Asians living in Singapore. Results: The Global Lung Initiative (GLI) and National Health and Nutrition Examination Survey consistently overestimated expiratory volumes (best fit GLI-African American, mean±sd z-score: FEV1 −0.94±1.05, FVC −0.91±1.10; n=7453). Age, height and weight were strong predictors of lung function in our participants (p<0.001), and sex-specific reference equations using these three variables were highly accurate in both internal validation (z-scores: FEV1 0.03±0.99, FVC 0.04±0.97, FEV1 /FVC −0.03±0.99) and external validation (z-scores: FEV1 0.31±0.99, FVC 0.24±0.97, FEV1 /FVC 0.16±0.91). Further adjustment for study regions improves the model fit, with highest accuracy for estimation of region-specific lung function in South Asia. Conclusion: We present improved equations for predicting lung function in South Asians. These offer the opportunity to enhance diagnosis and management of acute and chronic lung diseases in this major global population. Newly derived spirometry reference equations greatly improve prediction of normal lung function in South Asians, thus filling the long-standing gap of appropriate reference values for this ethnic group https://bit.ly/3H7ZGt5